Constraints on the Origin of Gold in the Meguma Zone, Ecum Secum area, Nova Scotia - Henderson, M.; Henderson, J. (Atlantic Geology, 1986)
Gold occurs mainly In laminated bedding-parallel quartz veins in the Goldenvllle Formation metawacke-slate sequence. The bedding-parallel veins formed by hydraulic fracturing before the beds were folded. Subsequently, during development of the folds, en echelon quartz veins formed on the fold limbs, and perhaps in the latest stage of folding, saddle reef veins formed along fold hinges. All these vein types are locally auriferous, but gold was first deposited during formation of the bedding-parallel veins. Absence of any through-going system of "feeder" veins as well as the formation of hydraulic fractures indicate that the rocks were not permeable during vein formation, and the quartz and gold were derived locally from the host strata.